PENGARUH TINGKAT KESEHATAN BANK TERHADAP RETURN SAHAM DI BURSA EFEK INDONESIA (BEI) - Daniel Kurniadi (MIX: JURNAL ILMIAH MANAJEMEN, 2013)
Abstract: This study aims to determine how the effect of CAMELS ratios consisting of Capital Adequacy Ratio, Return on Asset, Operating Expense to Operating Income, Earnings Per Share, and the Loan to Debt Ratio on stock returns banking companies listed in Indonesia Stock Exchang. The research method used is a ratio measurement consisting of the Capital Adequacy Ratio, Return on Asset, Operating Expense to Operating Income, Earnings Per Share, and the Loan to Debt Ratio and themeasurement of stock returns. After that tested the model by using the Fixed Effect Model to determine the effect of independent variables on the dependent variable. Results of this study indicate that a significant difference between the ratios of CAMELS on stock returns. Partially, there is a significant relationship between the Loan to Debt Ratio and stock return in the previous year on stock returns. The conclusion that can be given is the Loan to Debt Ratio and stock return in the previousyear can be used by investors as an analytical tool that helps in predicting stock returns.Keywords: CAMELS Ratio, Stock Retur